Od margine k širšim družbenim spremembam - Jurančič Šribar, Luna (Socialno delo, 2018)
The article is based on more than ten years of working experiences in the Association for help and self-help of homeless people Kings of the Street. There, different innovative programmes for facing the problem of homelessness have been developed (street paper, resettlement support, anti-eviction programme, day centre, fieldwork ...), and recently the attention has been drawn to developing the field of social economy together with homeless people. With the development of an alternative economic system, the question is how marginalized groups of people can gather their strengths, and use their resources for their autonomous existence and survival. This article is particularly focused on the obstacles which emerged during the time of establishing such a community. Finally, alternative modes of cooperation in the framework of social economy are presented.
Keywords: social economy; socialna ekonomija; brezdomni; homeless people; Kings of the Street; Kralji ulice; marginalisation; marginalizacija; media; mediji; communication medium